Interaction design in E-learning using Kansei Engineering / Pura Anak Sipok - Sipok, Pura (2012)
E-learning exploits interactive technologies and communication systems to improve the learning experience. It has the potential of transforming the way students learn. It can raise standards, and widen participation in lifelong learning. It has been discovered that emotion can affect the learning experience. However, understanding the emotional reaction of student in a complicated learning environment is challengeable task. The effect of interactivity on students learning still yields different result. There are still some who claimed there are the advantages of interactivity, while others claimed mixed results of interactivity. Therefore, it can be argued that there is still room for more research in this area. Especially in order to recognize which element of interactivity helps student learning, and which is not. Thus, this research aims to propose an interaction design for E-learning to make it more interactive and attractive to all students. Kansei Engineering method is used in this research, to achieve the solution to the problem. The method is used to analyze the relationships of students' emotional responses and interaction design elements in E-learning. The data analyze from Kansei Engineering method is use to propose a guide on interaction design of Kansei E-learning applications. The recommendation of interaction design for E-learning applications will contribute to the body of knowledge of E-learning specifically to the emotional design. Students' attention also can be capture by instigating emotional connectivity to the E-learning applications. A propose guide can help the designers to develop interactive and attractive courses.